The chain mediation effect of rumination and worry between the intentionality and content dimensions of mind wandering and internalizing symptoms of depression and anxiety - Siqing Guan; Toru Takahashi; Nozomi Tomita; Hiroaki Kumano (Scientific Reports)
Abstract Rumination and worry, as maladaptive emotion regulation strategies, perpetuate internalizing symptoms of depression and anxiety. However, examinations of dysfunctional mind wandering (MW)—internally oriented thoughts that contribute to emotion dysregulation—and its underlying the cognitive mechanisms related to internalizing symptoms remains limited. This study aimed to identify dysfunctional types of MW associated with internalizing symptoms of depression and anxiety by distinguishing between the intentionality and content of MW. The results indicate that trait rumination and worry sequentially mediate the relationship between the frequency of unintentional MW, which encompasses vague, future-oriented, and negative content, and internalizing symptoms. Furthermore, both single and chained mediation effects were identified in the relationship between unintentional negative MW and internalizing symptoms, with worry acting either as a sole mediator or as a subsequent mediator following rumination in a chain mediation pathway. This study offers novel insight into the distinct roles of rumination and worry as maladaptive emotion regulation strategies, particularly regarding dysfunctional MW types and their contributions to internalizing symptoms of depression and anxiety.